(untitled) (Global Journal of Human-Social Science, 2015)
The study was an assessment of teachers’ academic disciplines and their dispositions to some affective characteristics like values orientation, work attitude, motivation, and needs satisfaction. The study which adopted survey design used a sample of 1062 teachers selected from an estimated population of 21,240 teachers spread across the 203 public secondary schools in Cross River State of Nigeria. An instrument called Teachers’ Affective Characteristics Questionnaire was used for data collection. The data were analysed using One-Way Analysis of Variance (ANOVA) test statistic. Results of the study showed that teachers’ academic disciplines significantly influence their dispositions to affective characteristics. It was concluded that, it was teachers with education disciplines that were more disposed to affective characteristics than their counterparts with non-education disciplines. The study concludes that teachers should be encouraged to pick higher degrees in education after their first degrees as this will improve their work values, work attitude, motivation and needs satisfaction (also considered in this study as job satisfaction).